A Phase 3, Randomized, Double‐Blind, Placebo‐Controlled Study to Determine the Effect of Romiplostim on Health‐Related Quality of Life in Children with Primary Immune Thrombocytopenia and Associated Burden in Their Parents. Issue 7 (1st April 2016) - Mathias, Susan D.; Li, Xiaoyan; Eisen, Melissa; Carpenter, Nancy; Crosby, Ross D.; Blanchette, Victor S.
Abstract : Background: Chronic immune thrombocytopenia (ITP) in children can negatively impact their health‐related quality of life (HRQoL) and impose a burden on their parents. This study sought to examine the effect of romiplostim on HRQoL and parental burden in children with primary ITP. Procedure: This was a phase 3, randomized, double‐blind, placebo‐controlled study. Children aged <18 years with ITP ≥6 months were randomly assigned to receive romiplostim or placebo for 24 weeks. The Kids' ITP Tool (KIT) was used to measure HRQoL and was administered to patients and/or their parents at baseline and weeks 8, 16, and 25. Mean KIT scores at each assessment and mean changes in KIT scores from baseline were calculated overall by treatment group and platelet response status. Psychometric properties of the KIT were evaluated and the minimally important difference (MID) was estimated for different KIT versions. Results: Sixty‐two patients (42 romiplostim and 20 placebo) were enrolled. Changes in KIT scores by treatment group showed numerically greater and more often statistically significant improvements from baseline to each assessment for children receiving romiplostim versus placebo. Mixed‐effects analysis demonstrated statistically significantly greater reduction in parental burden from baseline in the romiplostim group versus placebo. Ranges for the MID were estimated as 9–13 points for the Child Self‐Report version and 11–13 points for the Parent Impact version. Conclusions: The treatment with romiplostim may be associated with improved HRQoL in children with primary ITP and reduced burden to their parents.